5-(2, 6-Bis((E)-4-(dimethylamino)styryl)-1-ethylpyridin-4(1H)-ylidene)-2, 2-dimethyl-1, 3-dioxane-4, 6-dione: aggregation-induced emission, polymorphism, mechanochromism, and thermochromism. Issue 36 (21st August 2017) - Zhou, Yibin; Qian, Lebin; Liu, Miaochang; Huang, Xiaobo; Wang, Yuxiang; Cheng, Yixiang; Gao, Wenxia; Wu, Ge; Wu, Huayue
Abstract : A new 1, 4-dihydropyridine derivative was reported to display intriguing multifunctional photophysical properties. Abstract : Herein, we report the synthesis of a new 1, 4-dihydropyridine derivative containing 2, 2-dimethyl-1, 3-dioxane-4, 6-dione and N, N -dimethylaniline. This compound exhibits aggregation-induced emission properties due to its highly twisted conformation and it has three crystalline polymorphs, which exhibit yellow (DHPM- y ), orange (DHPM- o ), and red (DHPM- r ) fluorescence. The different emissions of the polymorphs mainly depend on their molecular conformations due to the weak intermolecular interactions, as revealed by single crystal structural analysis. More importantly, these three crystalline polymorphs show different mechanochromic phenomena under varying pressure. The fluorescent color changes inDHPM- o andDHPM- r upon gentle grinding are attributed to a crystal-to-crystal transformation which alters their molecular conformations, whereas those ofDHPM- y andDHPM- o upon strong grinding are ascribed to the transformation from a crystalline state to an amorphous state. Additionally, DHPM- y andDHPM- o also display thermochromic properties. These results will provide useful information for obtaining intriguing multifunctional fluorescent materials by rational modification of classic luminogens.